2021
DOI: 10.1186/s12891-021-04472-6
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation in the OPG/RANK/RANKL pathway is associated with steroid-induced osteonecrosis of the femoral head

Abstract: Background Dysregulation of the OPG/RANK/RANKL signalling pathway is a key step in the occurrence of steroid-induced osteonecrosis of the femoral head (ONFH). This study aims to understand the degree of methylation of the OPG, RANK, and RANKL genes in steroid-related ONFH. Methods A case-control study was designed, including 50 patients (25 males and 25 females) and 50 matched controls. The European Molecular Biology Open Software Suite (EMBOSS) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The results indicated that the increase in ROS was proportional to the number of osteoclasts. Sun et al.’s study ( 18 ) also supported this finding. Moreover, the excessive production of ROS reduces the synthesis of vasodilators, leading to the formation of microthrombi in endothelial cells, which block local blood vessels and cause ischemic necrosis in the femoral head’s neurovascular supply area, further exacerbating bone cell damage.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The results indicated that the increase in ROS was proportional to the number of osteoclasts. Sun et al.’s study ( 18 ) also supported this finding. Moreover, the excessive production of ROS reduces the synthesis of vasodilators, leading to the formation of microthrombi in endothelial cells, which block local blood vessels and cause ischemic necrosis in the femoral head’s neurovascular supply area, further exacerbating bone cell damage.…”
Section: Discussionmentioning
confidence: 58%
“…( 17 ) and Sun et al. ( 18 ) found that high levels of ROS lead to increased activity and numbers of osteoclasts, and inhibiting ROS levels and excessive osteoclast activity can prevent or alleviate the progression of steroid-induced SONFH. Therefore, further investigation of SOD2 can elucidate its role in the mechanism of femoral head ischemic necrosis, and antioxidant therapy may help prevent and control the progression of GC-induced femoral head ischemic necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the dysregulation of the OPG/RANK/RANKL signaling pathway is a key step in the occurrence of steroid-induced ONFH [ 28 ]. miR-34a has been found to alleviate steroid-induced ONFH through regulating the OPG/RANK/RANKL signaling pathway [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of the expression of these genes is known to be a key link in the development of steroid-induced osteonecrosis of the femoral head and was noted to be associated with increased DNA methylation levels of OPG and RANK genes and with decreased levels in the RANKL gene (Sun et al, 2021). Previously, J.…”
Section: Introductionmentioning
confidence: 99%